PERTANGGUNGJAWABAN TINDAK PIDANA TURUT SERTA SEBAGAI MATA PENCAHARIAN MEMPERMUDAH DILAKUKANNYA PERBUATAN MELANGGAR KESUSILAAN OLEH ORANG LAIN DENGAN ORANG KETIGA - Puspa Ramadhani, Dea; Hartono, Bambang; , Ansori (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
Prostitution is widespread in Indonesia like other forms of a moral crime, and cyberspace is no exception. Internet crimes related to prostitution are increasing along with the rapid advancement of (online) technology. In the case of pimps related to prostitution, the unlawful act of allowing others to commit acts of violating decency by a third person can be seen in the Decision of the Supreme City District Court Number: 144/Pid.B/2022/PN. Kot. This normative juridical research is carried out by classifying various related legal materials, then the legal materials are described and evaluated qualitatively; systematically compiled to give an overview and draw certain conclusions as problem solving. The results showed that economic factors play an important role in motivating perpetrators to engage in criminal behavior and making it easier for other perpetrators to commit immoral acts with others. Some of the factors that cause prostitution include lack of education (those who do not go to school are more likely to engage in prostitution) and lack of public legal awareness (what is prohibited in the Criminal Code is not always clear to society).